Analisis Perbandingan Kinerja Keuangan Bank Syariah dan Bank Konvensional - Gina Putri Awaliah; Oka Barokah; Lathifuddin Lathifuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The objective of this study is to examine and compare the financial performance of Islamic banks and conventional banks in Indonesia during the 2019–2023 period. This research is motivated by the rapid growth of the Islamic banking industry; however, its market share remains relatively small compared to conventional banks. The study evaluates various financial ratio indicators, including Return on Assets (ROA), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), BOPO, Non-Performing Loans (NPL), and Non-Performing Financing (NPF), using a quantitative approach and comparative method. Data were collected from the annual financial reports of several major banks selected through purposive sampling. The results of the analysis indicate that conventional banks generally outperform in terms of profitability and operational efficiency, as reflected in the ROA and BOPO ratios. On the other hand, Islamic banks demonstrate more stable financing quality and liquidity, as indicated by relatively stable NPF and FDR ratios. These performance differences stem from the distinct operational principles of the two banking systems: interest-based operations for conventional banks and profit-sharing principles for Islamic banks. The study concludes that a more comprehensive evaluation method, integrating both sharia compliance and financial elements, is essential to provide a fair and accurate assessment of bank performance. The findings are expected to be valuable for regulators, academics, and industry practitioners in formulating policies that support a more inclusive and sustainable banking system.